Familial predisposition and susceptibility to the effect of other risk factors for myocardial infarction. Issue 5 (1st May 1999) - Hippe, M; Vestbo, J; Hein, H O; Borch-Johnsen, K; Jensen, G; Sørensen, T I
Abstract : STUDY OBJECTIVES: To assess if familial predisposition to myocardial infarction (MI) is an indicator of increased susceptibility to the effect of other established risk factors. The study assessed whether a family history of MI modifies the effect of arterial blood pressure, plasma cholesterol, high and low density lipoprotein cholesterol, % triglycerides, diabetes mellitus, body mass index, height, smoking habits, alcohol intake, physical activity level, and educational level on the incidence of MI. DESIGN: Prospective population based cohort study of cardiovascular risk and risk factors with follow up of MI by record linkage with the Cause of Death Register and The National Hospital Discharge Register until 1994. SETTING: The Copenhagen Centre for Prospective Population Studies, where data from three Danish studies are integrated. PARTICIPANTS: Subjects were 24, 664 people aged 20-93, examined between 1976 and 1987. MAIN RESULTS: A total of 1763 new cases of MI occurred during 293, 559 person years of observation. All risk factors, including family history of MI reported by 4012 subjects, were, as expected, associated with incidence of MI. With a few inconsistent exceptions we found no significant interactions between family history of MI and cardiovascular risk factors in their effect on MI. CONCLUSIONS: The familial predisposition to MI does not consistently modify the effect of other risk factors on the risk of MI. However, subjects with a family history of MI may still be regarded as an appropriate target group for screening for cardiovascular risk and intervention against other risk factors.